2015
DOI: 10.1177/0734282915573723
|View full text |Cite
|
Sign up to set email alerts
|

Implications for Educational Classification and Psychological Diagnoses Using the Wechsler Adult Intelligence Scale–Fourth Edition With Canadian Versus American Norms

Abstract: Building on a recent work of Harrison, Armstrong, Harrison, Iverson and Lange which suggested that Wechsler Adult Intelligence Scale–Fourth Edition (WAIS-IV) scores might systematically overestimate the severity of intellectual impairments if Canadian norms are used, the present study examined differences between Canadian and American derived WAIS-IV scores from 861 postsecondary students attending school across the province of Ontario, Canada. This broader data set confirmed a trend whereby individuals’ raw s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 24 publications
8
26
0
Order By: Relevance
“…With similar results in their studies using a referred sample, Harrison et al (2014, Harrison et al, 2015 have suggested that small Canadian sample sizes may explain the occurrence of lower scaled scores in Canada compared with that in the United States. This suggestion has not been supported in empirical studies and is not consistent with the robust finding of U.S.-Canadian differences across varying sample sizes (see Wechsler, 1996Wechsler, , 2001Wechsler, , 2004aWechsler, , 2008aWechsler, , 2012Wechsler, , 2014a.…”
Section: Differences In Wais-iv Canadian and Us Normsmentioning
confidence: 65%
See 4 more Smart Citations
“…With similar results in their studies using a referred sample, Harrison et al (2014, Harrison et al, 2015 have suggested that small Canadian sample sizes may explain the occurrence of lower scaled scores in Canada compared with that in the United States. This suggestion has not been supported in empirical studies and is not consistent with the robust finding of U.S.-Canadian differences across varying sample sizes (see Wechsler, 1996Wechsler, , 2001Wechsler, , 2004aWechsler, , 2008aWechsler, , 2012Wechsler, , 2014a.…”
Section: Differences In Wais-iv Canadian and Us Normsmentioning
confidence: 65%
“…The second component tests the claim from the Harrison et al (2014, Harrison et al, 2015 studies that the proportion of their clinical samples scoring below specific FSIQ cut-points using Canadian norms is higher than that should be expected, and related to this, that the percentage of cases scoring at these same cut-points using the U.S norms is a more accurate depiction of their sample. Here, examples are presented to illustrate the impact of a smaller SD and higher mean on Canadian scaled scores versus U.S. scaled scores.…”
Section: The Current Studymentioning
confidence: 99%
See 3 more Smart Citations